2013
DOI: 10.1021/nl4033439
|View full text |Cite
|
Sign up to set email alerts
|

Local Mechanical Properties of Electrospun Fibers Correlate to Their Internal Nanostructure

Abstract: The properties of polymeric nanofibers can be tailored and enhanced by properly managing the structure of the polymer molecules at the nanoscale. Although electrospun polymer fibers are increasingly exploited in many technological applications, their internal nanostructure, determining their improved physical properties, is still poorly investigated and understood. Here, we unravel the internal structure of electrospun functional nanofibers made by prototype conjugated polymers. The unique features of near-fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 46 publications
(91 reference statements)
7
109
0
Order By: Relevance
“…The cavities form because of the nature of the chemical bonding at that interface, which is comparatively weak due to the nanoparticle surface chemistry and the processing conditions used in this study. 45 Direct visualization of such cavities around nanoparticles in structural composites via optical or transmission electron microscopy remains challenging, 3,8,10,[32][33][34] especially in the early stages of void formation. The LSM simulation provides a facile way to qualitatively model this effect, albeit in two dimensions, in partially phase-separated nanocomposites where the Young's modulus is lowered when a higher stiffness filler is added.…”
Section: Introductionmentioning
confidence: 99%
“…The cavities form because of the nature of the chemical bonding at that interface, which is comparatively weak due to the nanoparticle surface chemistry and the processing conditions used in this study. 45 Direct visualization of such cavities around nanoparticles in structural composites via optical or transmission electron microscopy remains challenging, 3,8,10,[32][33][34] especially in the early stages of void formation. The LSM simulation provides a facile way to qualitatively model this effect, albeit in two dimensions, in partially phase-separated nanocomposites where the Young's modulus is lowered when a higher stiffness filler is added.…”
Section: Introductionmentioning
confidence: 99%
“…It is a lipophilic drug (partition coefficient log P > 5) with a large molecular weight of 307.41 g/mol and a poor aqueous solubility of <0.1 g/100 mL and is expected to show poor transport across the skin [6,7]. Recently, much research has been focused on fabricating three-dimensional nano fibers for applications in tissue engineering, catalysis, biosensors, skin regeneration, and wound healing by virtue of their extensive surface-to-volume ratio, peculiar morphology, sufficient mechanical strength, and plentiful porosity [8,9]. It is emphasized that the high surface area of nanofibers expedite proper gaseous exchange, charter fluid accumulation, or retention, of wound fluid, maintain moisture balance, and preserve aseptic conditions [10], which are eminently fascinating properties in the mitigation of infectious wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, investigation on the one-dimensional luminescent-electrical-magnetic multifunctional materials has become one of the hot spots in the field of materials science [2,3] . As far as we know, some studies of multifunctional composite nanofibers have been reported.…”
Section: Introductionmentioning
confidence: 99%